PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA DOSEN TETAP PADA STIKES DHARMA HUSADA BANDUNG - Kadir, Kadir; Pamungkas, Gugum (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The purpose of this study was to: (1) to find the motivation to work STIKes Dharma Husada Bandung (2) to determine the organizations culture STIKes Dharma Husada Bandung (3) to determine the compensation STIKes Dharma Husada Bandung (4) to determine the performance of tenured faculty in STIKes Dharma Husada Bandung (5) to determine the effect of motivation on the performance of tenured faculty in the College of Health Sciences Dharma Husada Bandung (6) to determine the effect of organizational culture on the performance of tenured faculty in the College of Health Sciences Dharma Husada Bandung (7) to determine the effect of compensation on the performance of tenured faculty The College of Health Sciences Dharma Husada Bandung (8) to determine the effect of work motivation, organizational culture and compensation jointly on the performance of tenured faculty in the College of Health Sciences Dharma Husada Bandung In this study took a sample of 56 permanent lecturers. The results of the research are: Work Motivation Lecturer in Bandung categorized Husada STIKes Dharma well. It is seen from the achievement criteria score of 4.16. Organizational Culture on STIKes Dharma Husada Bandung is in either category. It is seen from the achievement criteria score of 3.70. Compensation for lecturer in Bandung Husada STIKes Dharma is the good category. It is seen from the achievement scores of 4.00. Lecturer performance level STIKes Dharma Husada Bandung categorized either. It is seen from the achievement criteria score of 4.02. Influence on the Performance of Work Motivation lecturer at Dharma STIKes Husada Bandung, directly is by 0133, through Organizational Culture for 0012, through the Compensation for 0099. So the total effect by 0244 or by 24.4%. Influence of Organizational Culture on Performance STIKes lecturer at Bandung Husada Dharma, directly by 0034, over 0,031 Compensation, through Work Motivation of 0,012. So the total effect of 0.077 or 7.7%. Effect of Compensation to Performance STIKes Dharma Lecturer at Husada Bandung, directly by 0290, through Organizational Culture 0031, through the work motivation of 0099. So the effect of a total of 0420 or by 42%. Simultaneously influence Work Motivation, Organizational Culture and Performance Compensation for STIKes Dharma Lecturer at Husada Bandung is the strong category which is equal to 0.741 or 74%, This shows that significant influence.